2016
DOI: 10.1080/16070658.2016.1198608
|View full text |Cite
|
Sign up to set email alerts
|

The food environment of students on a financial assistance programme at the University of the Free State, Bloemfontein

Abstract: The research study was undertaken to determine the food that students on the financial assistance program at the University of the Free State, Bloemfontein, could buy on campus. Students on this program can buy food from six food outlets on campus from their daily allowance. The types of foods sold were mostly sugar-containing products. The availability of healthy food choices should be promoted in an environment where food assistance programs are offered to students. Objectives: Enrolment at institutions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…40 The food environment of South African universities should also be assessed. 41 Specifically, students have claimed that fruits and vegetables are not easily available on campus. 41 , 42 Based on past successful interventions amongst South African youth, 43 campaigns should be implemented across universities.…”
Section: Discussionmentioning
confidence: 99%
“…40 The food environment of South African universities should also be assessed. 41 Specifically, students have claimed that fruits and vegetables are not easily available on campus. 41 , 42 Based on past successful interventions amongst South African youth, 43 campaigns should be implemented across universities.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the included study characteristics, including assessment type, focus, and scope, is shown in Table 1. Eighteen studies were conducted in the United States [6][7][8][9][10]13,17,18,24,[30][31][32][33][34][38][39][40][41], four in Australia [15,28,42,43], three in Brazil [14,27,44], two in Canada [12,45], and one in Egypt [46], Ghana [47], Italy [48], Lebanon [49], New Zealand [50], Norway [51], Spain [11], South Africa [52], and United Arab Emirates [29]. Thirteen studies compared multiple higher education institutions [6][7][8][9]13,15,28,29,38,43,[49]…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Twenty-one studies reported results of an institutional-level audit: eight audited campus eateries [6,7,12,14,27,38,44,52], four examined vending machines [11,13,17,29], one reviewed food stores [8], and eight had a combination of outlet types [10,15,28,41,42,[45][46][47]. Two studies detailed the changes to a university food environment over time [12,27], whereas all other studies described the food environment at one time point.…”
Section: Institutional-level Articlesmentioning
confidence: 99%
“…Investigations into the types of food that students self-reportedly eat have found that students eat food of low nutritional quality (Kassier and Veldman 2013;Munro et al 2013;Steenkamp et al 2016). While this could be attributed to a lack of knowledge about nutrition (Ndlovu 2017), the issue is exacerbated by limited access to healthy food at university campuses (Meko and Jordaan 2016).…”
Section: Student Hunger In South Africamentioning
confidence: 99%